Anti-Apoptotic Effects of 3,3’,5-Triiodo-L-Thyronine in the Liver of Brain-Dead Rats - Rebolledo, Rolando A.; Van Erp, Anne C.; Ottens, Petra J.; Wiersema-Buist, Janneke; Leuvenink, Henri G. D.; Romanque, Pamela (PLOS ONE, 2015)
Background Thyroid hormone treatment in brain-dead organ donors has been extensively studied and applied in the clinical setting. However, its clinical applicability remains controversial due to a varying degree of success and a lack of mechanistic understanding about the therapeutic effects of 3,3’,5-Triiodo-L-thyronine (T3). T3 pre-conditioning leads to anti-apoptotic and pro-mitotic effects in liver tissue following ischemia/reperfusion injury. Therefore, we aimed to study the effects of T3 pre-conditioning in the liver of brain-dead rats. Methods Brain death (BD) was induced in mechanically ventilated rats by inflation of a Fogarty catheter in the epidural space. T3 (0.1 mg/kg) or vehicle was administered intraperitoneally 2 h prior to BD induction. After 4 h of BD, serum and liver tissue were collected. RT-qPCR, routine biochemistry, and immunohistochemistry were performed. Results Brain-dead animals treated with T3 had lower plasma levels of AST and ALT, reduced Bax gene expression, and less hepatic cleaved Caspase-3 activation compared to brain-dead animals treated with vehicle. Interestingly, no differences in the expression of inflammatory genes (IL-6, MCP-1, IL-1β) or the presence of pro-mitotic markers (Cyclin-D and Ki-67) were found in brain-dead animals treated with T3 compared to vehicle-treated animals. Conclusion T3 pre-conditioning leads to beneficial effects in the liver of brain-dead rats as seen by lower cellular injury and reduced apoptosis, and supports the suggested role of T3 hormone therapy in the management of brain-dead donors.